PENGATURAN HUKUM PENGGUNAAN MEREK KOLEKTIF TERDAFTAR BERDASARKAN PASAL 79 UNDANG-UNDANG NOMOR 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS - Dewi, Ni Made Trisna; Ida Bagus Bayu Brahmantya; Kadek Yoga Artha Diputra (Kerta Dyatmika, 2024)
Intellectual Property Rights (IPR) are the result of human intellectual activity expressed in the form of creations, works of art, designs, or inventions that are beneficial to human life. One form of IPR is a trademark, which functions as a sign affixed to a product to distinguish it from others, although it is not part of the product itself. Juridically, the requirements for trademark registration are governed by Article 4 of Law Number 20 of 2016 concerning Trademarks and Geographical Indications. This study aims to examine the legal regulation of the use of trademarks that are inconsistent with those registered, and to provide legal certainty regarding the use of registered collective marks pursuant to Article 79 of the aforementioned Law. The research employs a normative legal method. The results of the study indicate that Article 79 contains vague legal norms, particularly in its reference to the principle of mutatis mutandis, which is not clearly or explicitly defined, thereby creating potential for multiple interpretations. The conclusion of this study is that trademark registration strengthens the legal position of trademark holders in filing lawsuits and resolving trademark disputes before the court. In the business context, legal certainty in trademark registration also enhances investor confidence and provides assurance in conducting investment activities.